Search for the Standard Model Higgs Boson in the Missing Energy and Acoplanar b-Jet Topology at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Klima, B.; et al. (Amer Physical Soc, 2008)
We report a search for the standard model Higgs boson in the missing energy and acoplanar b-jet topology, using an integrated luminosity of 0.93 fb(-1) recorded by the D0 detector at the Fermilab Tevatron p (p) over bar Collider. The analysis includes signal contributions from p (p) over bar -> ZH -> v (v) over barb (b) over bar, as well as from WH production in which the charged lepton from the W boson decay is undetected. Neural networks are used to separate signal from background. In the absence of a signal, we set limits on sigma(p (p) over bar -> VH) x B(H -> b (b) over bar) at the 95% C.L. of 2.6-2.3 pb, for Higgs boson masses in the range 105-135 GeV, where V W, Z. The corresponding expected limits range from 2.8 to 2.0 pb.